Pancasila and Rukun Negara: A Relation of Identity, State, and Nationalism in Indonesia and Malaysia - Dwijayanto, Arik; Multazam, Dawam (Fakultas Agama Islam, Universitas Hasyim Asy'ari, 2021)
This article will elaborate on Indonesia’s Pancasila and Malaysia’s Rukun Negara, the state base for both neighbouring Southeast Asian countries. Concerning the relation between identity, State, and nationalism through a literature study approach, this article found that the socio-historical setting of the birth of Pancasila and Rukun Negara influences the process of identity formation and the spirit of nationalism in both countries. Besides, the success of the two ideologies of the State in shaping the identity and spirit of nationalism is supported by the representation of structural and cultural elites. Furthermore, the manifestation of Pancasila and Rukun Negara is done in various fields to become the way of life of Indonesian and Malaysian society, which finally become the amplifier of awareness in shaping nationalism identity and spirit of nationalism in both countries. Finally, taking into account a wide range of issues to be faced by both countries, this article suggests that Pancasila and Rukun Negara can eventually become a national identity and a spirit in shaping the nationalism of citizens in Indonesia and Malaysia.